2019
DOI: 10.1177/2158244019876265
|View full text |Cite
|
Sign up to set email alerts
|

On the Servant Leadership Behaviors Perceived in Voluntary Settings: The Influences on Volunteers’ Motivation and Organizational Commitment

Abstract: Building on the functional approach theory, the current study empirically examined the influences of servant leadership behaviors on volunteers’ motivations and on their organizational commitment feelings. In addition, it also examined servant leadership’s indirect influences via those motivations on volunteers’ commitment feelings. To test its hypotheses, the study used the data collected from 385 volunteers. The research has found out that the degree of perceived servant leadership behaviors affected both pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
21
1
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 23 publications
(23 citation statements)
references
References 70 publications
(96 reference statements)
0
21
1
1
Order By: Relevance
“…The exchange relationship is an intervening construct between two partners, and the character of the relationship will define the consequences (Cropanzano & Mitchell, 2005, Erdurmazlı, 2019. Trust is a promising relational construct in a work setting between two interacting individuals (Dirks & Ferrin, 2002), and it is a key component in a successful relationship between a leader and followers.…”
Section: Trust As a Mediatormentioning
confidence: 99%
See 1 more Smart Citation
“…The exchange relationship is an intervening construct between two partners, and the character of the relationship will define the consequences (Cropanzano & Mitchell, 2005, Erdurmazlı, 2019. Trust is a promising relational construct in a work setting between two interacting individuals (Dirks & Ferrin, 2002), and it is a key component in a successful relationship between a leader and followers.…”
Section: Trust As a Mediatormentioning
confidence: 99%
“…Trust is a promising relational construct in a work setting between two interacting individuals (Dirks & Ferrin, 2002), and it is a key component in a successful relationship between a leader and followers. It helps them cooperate, manage, share, and enable mutual understanding (Dirks & Ferrin, 2002;Erdurmazlı, 2019). It also reflects the level of confidence of one person in the competence and skill of another (Nyhan & Marlowe, 1997).…”
Section: Trust As a Mediatormentioning
confidence: 99%
“…Previous studies have confirmed the benefits of servant leadership and LMX in an all‐volunteering context for respectively volunteers' motivation, satisfaction, commitment, and intentions to stay in the organization (Erdurmazlı, 2019; Schneider & George, 2011); and volunteers' job satisfaction and intentions to stay with the organization (Bang, 2011).…”
Section: Leadership In All‐volunteer Nonprofit Organizations: a Briefmentioning
confidence: 82%
“…Further, servant leaders influence others through: building trusting relationships; demonstrating an altruistic mind set; and possessing interpersonal competence. Patterson (2003) highlighted love, humility, altruism, vision, trust, empowerment and service as important values held by servant leaders, which are also the hallmarks of servant leaders ( Erdurmazlı., 2019 ).…”
Section: Servant Leadership Frameworkmentioning
confidence: 99%
“…It has been argued that volunteer leaders are more concerned with the development of people, engage in inspiring leadership behaviours, even more than paid leaders, and are more psychologically involved by demonstrating values that promote independent thought and challenge ( Benson, 2010 ; Catano et al., 2001 ; Posner, 2015 ). Servant leadership model has also been associated with motivations to volunteer ( Erdurmazlı., 2019 ), as well as leadership in African culture ( Wanasika et al., 2011 ). The servant leadership framework was therefore found relevant to the aim of the study, and to the specific study objectives given in the next section.…”
Section: Servant Leadership Frameworkmentioning
confidence: 99%